An analysis of professional discourses and gendered identities in Malaysian media - Yoong, Melissa (2018)
This thesis analyses the professional discourses and gendered identities of working women manifested within Malaysian media targeting a female audience. It also interrogates the ideologies of gender that inform, and are espoused by, these discourses and identities. Through the integration of feminist critical discourse analysis and feminist conversation analysis, it examines career advice texts and interviews with high-achieving women produced over a 12-month period in three print and broadcast media: Her World, a Malaysian magazine; Clove, a Sunday pullout in a mainstream newspaper; and Capital FM, a commercial radio station. The analysis of discourses expressed in the conception of women’s professional selves and occupational lives fills a discernible gap in gender and language research, as previous empirical work on media directed at women has largely emphasised on beauty, relationships, sex, and parenting.